Role of Ethylene in Lactuca sativa cv `Grand Rapids' Seed Germination - Abeles, Fred B. (1986)
Promotion of thermoinhibited (30°C) lettuce (Lactuca sativa cv `Grand Rapids') seed germination by ethylene is similar to the action of the gas in other hormonal systems. Ethylene was more active than propylene and ethane was inactive. An inhibitor of ethylene production, aminoethoxy-vinylglycine, reduced ethylene evolution and germination. Inhibitors of ethylene action such as, 5-methyl-7-chloro-4-ethoxycarbonylmethoxy-2,1,3-benzothiadiazole, 2,5-norbornadiene, and silver thiosulfate inhibited germination and the effect was reversed by the addition of ethylene to the gas phase. The action of ethylene appears to be due to the promotion of radial cell expansion in the embryonic hypocotyl. The action of N6-benzyladenine and fusiccocin, which also overcome thermoinhibition, appears to be due to a promotion of hypocotyl elongation. None of the germination promoters studied appeared to function by lowering the mechanical resistance of the endosperm to embryonic growth. Data presented here are consistent with the view that ethylene plays a role in lettuce seed germination under thermoinhibited and normal conditions.